Trabecular Metal Augments for Treatment of Acetabular Defects: A Systematic Review - Malahias, Michael-Alexander; Mancino, Fabio; Gu, Alex; De Martino, Ivan; Togninalli, Danilo; Bostrom, Mathias P.; Sculco, Peter K. (The Journal of Hip Surgery, 2021)
Severe acetabular bone defects during revision total hip arthroplasty are often treated with a hemispherical shell and highly porous modular metal augments. Several papers have been already published reporting on the clinical performance of trabecular metal (TM) augments combined with a hemispherical shell for the management of severe acetabular defects. However, no systematic review of the literature has been published to date. The U.S. National Library of Medicine (PubMed/MEDLINE), EMBASE, and the Cochrane Database of Systematic Reviews were queried for publications utilizing keywords pertinent to tantalum augments and TM (Zimmer Biomet, Warsaw, Indiana) augments, revision THA, clinical outcomes, and complications associated with these procedures. Fifteen articles were found to be suitable for inclusion in the present study, which included 769 revision cases where acetabular augments were used. The majority of acetabular bone defects were type 3 according to the Paprosky classification (type 2A in 58 cases, 7.2%; type 2B in 139 cases, 17.2%; type 2C in 72 cases, 8.9%; type 3A in 360 cases, 44.7%; and type 3B in 177 cases, 22.0%). The overall revision rate for the 769 acetabular revisions with augments was 5.7% (46 cases) at mean mid-term follow-up. The most common reasons for revision were dislocation (3.3%), periprosthetic joint infection (2.9%), and aseptic loosening (2.7%). TM augments combined with hemispherical shells were found to be effective in the treatment of moderate-to-severe acetabular bone defects with a 5% acetabular component revision rate at mean mid-term follow-up. The literature did not delineate whether pelvic discontinuity was associated with a higher risk of aseptic loosening after TM augment. Further studies are needed to clarify the impact of additional screw fixation on survival rates, and whether the type of augment (wedge augments, “flying buttress” augments, column augments), the configuration used, and the number of screws influence clinical and radiographic outcomes.
Keywords: trabecular metal augments; total hip arthroplasty; acetabular bone loss; revision arthroplasty; tantalum augments